SYNTHESIS, STRUCTURE, AND ANTITUMOR-ACTIVITY OF 1,3-DITHIOL AND 1,3-DITHIOLAN-2-YLIDENEMALONATOPLATINUM(II) COMPLEXES - SOHN, YS; KIM, KM; JEONG, JH; NOH, DY; LEE, CO; CHOI, SU (ELSEVIER SCIENCE INC, 1994)
1,3-Dithiol- and 1,3-dithiolan-2-ylidenemalonatoplatinum(II) complexes A(2)Pt(OOC)(2)C = CR(2) (A = NH3, cyclopropylamine (CPA) or A(2) = ethylenediamine(EDA), trans(+/-)-1,2-diaminocyclohexane(DACH); R(2) = -SCH = CHS-, -SCH2CH2S-) have been synthesized and subjected to in vivo assay for antitumor activity after characterization by means of elemental analysis, IR spectroscopy, and x-ray analysis. The molecular structure of (CPA)(2)Pt(OOC)(2)C = CSCH = CHS has been determined by x-ray diffraction: space group P2(1)/n, a = 7.955(1), b = 16.912(2), c = 15.116(2) Angstrom, beta = 102.74(1)degrees, z = 4, R = 0.032, R(w) = 0.035. Among the Pt(II) complexes studied, biscyclopropylamineplatinum(II) complexes both of the above-mentioned dicarboxylate leaving groups exhibited much higher antitumor activity against the leukemia L1210 cell line compared with the known cisplatin.